Community Partnership Program: The Improvement Of Chemical Teacher Professional Competencies In Developing Modul Teaching Materials Based On Integrated Guided Inquiry - Andromeda Andromeda (Pelita Eksakta, 2019)
The aim of the activity was to provide knowledge, insight and skills to the Padang Pariaman District MGMP chemistry teachers in developing teaching materials modules based on guided inquiry integrated experiments. The training activities were carried out with several activities, namely: (1) Presentation on developing teaching materials, designing chemistry modules based on guided inquiry experiments, and tips on writing teaching materials using microsof word; (2) Discussion of various matters relating to the material presented; (3) chemistry module making workshops based on guided inquiry integrated experiments; (4) conducting module trials at SMAN 1 Nan Sabaris, Padang Pariaman Regency; (5) mentoring and evaluation. After conducting a series of training, participants were able to design a module based on guided inquiry integrated experiments, and module drafts have been produced for several chemical topics. The results of the module trial showed that happy, active and motivated students to learn chemistry using the guided inquiry based module integrated experiments.